The Emergence of High-Stakes Accountability Policies in Teacher Preparation: An Examination of the U.S. Department of Education’s Proposed Regulations - Maria Teresa Tatto (Education Policy Analysis Archives/Archivos Analíticos de Políticas Educativas, 2016)
Using a sociological framework this articleexplores the emergence and possible consequences of the 2015 U.S. Department of Education’s proposed federal regulatory policy on teacher educationprogramsand alternative route providers.After describing the key features of the policy,we examine the research literature looking for evidence of the merits of accountability policies in improving teacher education and preparation quality and outcomes. Although there is some research evidence that increased accountability measures may indeed contribute to improving the quality and outcomes of teacher education and preparation, the conditions under which this happens are not straightforward. While the stated aim of the regulatory policy,to ultimately advance student learning,finds widespread support in the education community, research evidence points to a number of validity problemswiththe overall policy. Of particular concern is the policy’s attempts at establishinga direct link between teacher preparationgraduates’employment and pupil achievement. The policy as conceived could negatively impact program norms and resources and undermine the development of teachers’ human, cultural,and social capital. We discuss the accreditation challenges that the policy is likely to confront and implications for the future of teacher education and preparation accountability.